Examining the Social Appearance Anxiety and Self-Esteem Levels of Students of the Sport Management Department - TOPUZ, Ramazan; BAHADIR, Ziya; ERDOĞAN, Çağrı Hamdi (Asian Journal of Education and Training, 2019)
The aim of this research study is to investigate the social appearance anxiety and self-esteem levels of sports management department students concerning some variables. 328 students participated in research group, who were studying at Erciyes University Department of Sports Management, Faculty of Sport Sciences in the 2018-2019 academic year. The research was conducted with the survey model. In order to determine participant students’ social appearance anxiety and self-esteem levels, Social Appearance Anxiety Scale and Rosenberg's Self-Esteem Scale were used as data collection tools. In the analysis of the data SPSS program was used. According to the results of the research, it was determined that the social appearance anxiety and self-esteem levels of Sports Management department students are in the medium range. Also a statistically significant negative correlation was determined between the social appearance anxiety and self-esteem levels of the students. There were statistically significant differences in the social appearance anxiety levels of the sport management students concerning the gender, age, and the academic grade. However, there was statistically no significant difference concerning the sport branch, doing regular exercises, doing active sport, and average grades. As per the self-esteem levels of the sport management students; there was statistically no significant difference concerning the gender, age, sport branch, average grades, academic grades, doing active sport, and doing regular exercises.